2014
DOI: 10.1177/1088357614532498
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of the Direct Instruction Language for Learning Curriculum Among Children Diagnosed With Autism Spectrum Disorder

Abstract: Many children diagnosed with autism spectrum disorder (ASD) exhibit difficulties with complex language and social communication. Direct Instruction (DI) is an empirically supported curriculum designed to teach complex language skills to children with and at risk of learning disabilities. Only recently, the effectiveness of DI has been evaluated among children with autism. The present study evaluated the effectiveness of the DI Language for Learning curriculum among 18 children diagnosed with ASD. Immediate pos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
23
0
3

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(29 citation statements)
references
References 18 publications
2
23
0
3
Order By: Relevance
“…Procedural fidelity data indicate that the teachers implemented the curriculum with high integrity, and the participants' direct acquisition data from mastery tests replicate the results of other studies in which the curriculum was implemented by researchers or therapists in home or clinic settings (e.g., Shillingsburg et al 2014;Flores et al 2016).…”
Section: Discussionsupporting
confidence: 70%
See 2 more Smart Citations
“…Procedural fidelity data indicate that the teachers implemented the curriculum with high integrity, and the participants' direct acquisition data from mastery tests replicate the results of other studies in which the curriculum was implemented by researchers or therapists in home or clinic settings (e.g., Shillingsburg et al 2014;Flores et al 2016).…”
Section: Discussionsupporting
confidence: 70%
“…Several studies that have evaluated the effects of LL on language outcomes for children with ASD have produced promising results (e.g., Flores et al 2013;Flores and Ganz 2014;Flores et al 2016;Shillingsburg et al 2014). For example, Flores and Ganz (2014) compared the effectiveness of LL and discrete trial instruction for teaching language skills to children with ASD and found that participants who received LL performed significantly better on curriculum-based language assessments than those who received discrete trial instruction.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Motor signs may serve as markers for deficits in parallel or neighbouring brain systems important for the control of socialization and communication. 13 Measures of motor function tend to be more overtly observable than measures of more complex social and behavioral systems. 8 …”
Section: Introductionmentioning
confidence: 99%
“…Por el contrario, otros estudios señalan que, en primer lugar, el aprendizaje es más efectivo cuando se realiza de forma individual y mediante programas de instrucciones directas, es decir, el término conocido en inglés como Direct Instruction (DI), ya que mejoran e implementan su comprensión. Para después pasar a combinar con el trabajo en grupos cooperativos con sus iguales en un aula ordinaria, de esta forma aprenderán estrategias para las relaciones sociales (Flores y Ganz, 2007;Flores, Nelson, Hinton, Franklin, T., Strozier, Terry, Franklin, 2013;Roux, Dion, Barrette, Dupéré y Fuchs, 2015;Shillingsburg, Bowen, Peterman y Gayman, 2015;Braun, Austin y Ledbetter-Cho, 2017;Head, Flores y Shippen, 2018).…”
Section: Resultsunclassified